Characterisation and Biological Activities of Tinospora Crispa (Menispermaceae) Extract with Emphasis on Alkaloids - Azrulrizawati, Abd Hamid (2013)
A study was carried out on the characterisation and biological activities of Tinospora crispa extract with emphasis on alkaloids. Methanolic extraction, crude alkaloid fractionation and separation using different chromatographic techniques (open columns and preparative TLC) were used for isolation of pure compounds. The structure of the isolated compounds were elucidated by spectroscopic methods such as UV, IR, 1D (H, C, DEPTQ), 2D (COSY, HMQC, HMBC) NMR, MS and also by comparison with the literature. Twelve compounds were isolated from these plants comprising eight alkaloids and four nonalkaloid compounds. Six of the alkaloid, viz., N formylannonaine,N-formylnornuciferine, lysicamine, magnoflorine, columbamine and dihydrodiscretamine previously isolated from T.crispa and other species the genus Tinospora. In addition, one known alkaloid, liriodenine was found for the first time in this study. A novel alkaloid, 4,13-dihydroxy-2,8,9 trimethoxydibenzo[a,g]quinolizinium was isolated and its structure was established by modern spectroscopic technique. A biosynthethic route to this alkaloid is proposed. Another new compound isolated was aliphatic amine, N,N-dimetylhexadecan-1-amine. Three types of bioactivity studies, viz., acetylcholinesterase inhibitory, radical scavenging and antimicrobial studies were carried out on isolated compounds containing nitrogen. The quaternary protoberberine alkaloids; columbamine and dihydrodiscretamine were found to be potent acetylcholinesterase inhibitors. Most of the isolated quaternary alkaloids showed moderately (IC> 500-800 μg/mL) radical scavenging activity. Oxaporphine alkaloids, lysicamine, liriodenine and aliphatic amine inhibited the growth of the Gram-positive bacteria, Staphylococcus aureus (+) and Enterococcus faecalis (+). Aliphatic amine also exhibited inhibitory activity against Gram-negative bacteria, Proteus vulgaris (-) and Psuedomonas aeurogenosa (-). Results of the present biological activity investigation further points to the potential of this plant species as a good source of new AChE inhibitors. The antioxidant and antimicrobial properties of different compounds support documented traditional use of T. crispa in wound healing and treatment of rheumatic, diarrhoea, ulcers, itches and wounds.